EKSPLORASI RUMAH ADAT BATAK TOBA TERHADAP KONSEP BANGUN RUANG DI KELAS XII SMA NEGERI 1 GIRSANG SIPANGAN BOLON - Purnama Raya Anjelina Situmorang; Hardi Tambunan; Ruth Mayasari Simanjuntak (Afore : Jurnal Pendidikan Matematika, 2025)
This study aims to explore the integration of the Batak Toba traditional house as a contextual medium in teaching three-dimensional geometric concepts to twelfth-grade students at SMA Negeri 1 Girsang Sipangan Bolon. A qualitative approach was employed to observe how geometric shapes within the architectural structure of the traditional house—such as prisms, pyramids, and rectangular blocks—can be identified and utilized to enhance students’ understanding of spatial geometry. The results indicate that this culturally based learning approach significantly improves students’ conceptual comprehension, creativity, and learning motivation. Students find it easier to associate geometric forms with real-world structures, positively impacting their academic performance. Moreover, this method reinforces local cultural values and promotes active student engagement in the learning process. Teachers play a crucial role in facilitating the connection between mathematical concepts and cultural context. The study recommends further development of local-culture-based instructional media and teacher training to integrate indigenous knowledge into classroom learning. The integration of cultural elements in mathematics education has proven effective in creating meaningful learning experiences and fostering students' cultural identity.